1993
DOI: 10.1177/095632029300400503
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Metabolism and Anti-Influenza Activity of 1,3,4-Thiadiazol-2-Ylcyanamide (LY217896)

Abstract: LY217896 (1,3,4-thiadiazol-2-ylcyanamide) is a 2-substituted thiadiazole that is an effective inhibitor of influenza A and B viruses in vitro and in the mouse infection model. The in vitro anti-influenza activity of LY217896 is reversed by a 10-fold excess amount of guanine or guanosine. LY217896 (1 or 10μg ml−1) effected a selective 60% decrease in the levels of intracellular pools of GTP in MDCK cells. The extent of cytotoxicity of LY217896 is positively correlated with the amount of LY217896 metabolite form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 33 publications
3
23
0
Order By: Relevance
“…The mechanism of action of ribavirin is due, in part, to its phosphorylation to the monophosphate, which can then inhibit IMPDH (Streeter et al, 1973(Streeter et al, , 1977Wray et al, 1985). Consistent with this is the observation that the antiviral activity of ribavirin can be reversed by excess guanosine (Streeter et al, 1973;Colacino et al, 1993) and by inosine and xanthosine (Streeter et al, 1973). Mycophenolic acid, which is also an inhibitor of inosine monophosphate dehydrogenase, displays potent anti-HIV activity in vitro by limiting the rate of de novo synthesis of guanosine nucleotides, thereby inhibiting HIV reverse transcriptase activity (Ichimura & Levy, 1995).…”
Section: Inhibition Of Transcription Translation and Replicationsupporting
confidence: 62%
See 1 more Smart Citation
“…The mechanism of action of ribavirin is due, in part, to its phosphorylation to the monophosphate, which can then inhibit IMPDH (Streeter et al, 1973(Streeter et al, , 1977Wray et al, 1985). Consistent with this is the observation that the antiviral activity of ribavirin can be reversed by excess guanosine (Streeter et al, 1973;Colacino et al, 1993) and by inosine and xanthosine (Streeter et al, 1973). Mycophenolic acid, which is also an inhibitor of inosine monophosphate dehydrogenase, displays potent anti-HIV activity in vitro by limiting the rate of de novo synthesis of guanosine nucleotides, thereby inhibiting HIV reverse transcriptase activity (Ichimura & Levy, 1995).…”
Section: Inhibition Of Transcription Translation and Replicationsupporting
confidence: 62%
“…One was that influenza virus variants could not be selected in vitro for resistance to LY217896 or its sodium salt (Hayden et al, 1990; JC Tang & JM Colacino, personal communication) suggesting the lack of a virus-specific target. The other was that the antiviral activity could be reversed by adding a molar excess of either guanosine or guanine (Colacino et al, 1993). Previously, a related compound, 2-amino-1,3,4-thiadiazole, was shown to inhibit Sindbis virus replication in vitro (Malinoski & Stollar, 1981) and it was thought that this compound is converted to the mononucleotide form intracellularly, and as such it is a competitive inhibitor of inosine monophosphate dehydrogenase (IMPDH) with respect to the natural substrate, IMP (Nelson et al, 1977).…”
mentioning
confidence: 99%
“…1), is effective in vitro against influenza A and B viruses, respiratory syncytial virus (RSV), and parainfluenza virus type 3 (PIV3), and is therapeutically effective in the mouse model of infection (Colaoino et al, 1990) as well as in cotton rats infected with RSV or PIV3 (Wyde et al, 1990). However, there appeared to be little antiviral selectivity when the anti-influenza IC so (0.7Ilg ml") was compared to the oytotoxic concentration (1-3 Ilg mr') in rapidly dividing uninfected cells (Colacino et aI., 1990;Hayden et al, 1990;Colacino et al, 1993). Recently, the major metabolite of LY217896 was identified ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was shown that LY217896 effected a seleotive reduction of GTP pools in MOCK cells but not in LY'MOCK cells (MOCK cells selected for resistance to the toxicity of LY217896), which did not metabolize LY217896 (Colacino et al, 1993). It was proposed that a metabolite of LY217896 inhibits IMPOH resulting ultimately in the reduction of GTP pools (Colacino et al, 1990;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation